2013
DOI: 10.1177/1098612x13509081
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of behavioural changes in domestic cats during short-term hospitalisation

Abstract: We evaluated behavioural changes in domestic cats during a short-term hospitalisation using a novel cat demeanour scoring system. Thirty-five, healthy client-owned cats admitted for neutering were enrolled. Cats were housed in a standardised cat ward for a short-term hospitalisation period (3-5 days) and demeanour scores were recorded once daily. The scoring system classified cats into one of five behavioural groupings: friendly-and-confident, friendlyand-shy, withdrawn-and-protective, withdrawn-and-aggressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 27 publications
(61 reference statements)
0
37
0
2
Order By: Relevance
“…In the context of recent work by Zeiler et al (2013), showing the negative effects of a clinic environment on feline demeanor, it is perhaps unsurprising that pain assessment is confounded by high demeanor scores in non-painful cats. Interestingly, Calvo et al (2014) and Zeiler et al (2013) both commented on the possible interaction between demeanor and pain assessment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the context of recent work by Zeiler et al (2013), showing the negative effects of a clinic environment on feline demeanor, it is perhaps unsurprising that pain assessment is confounded by high demeanor scores in non-painful cats. Interestingly, Calvo et al (2014) and Zeiler et al (2013) both commented on the possible interaction between demeanor and pain assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Calvo et al (2014) and Zeiler et al (2013) both commented on the possible interaction between demeanor and pain assessment. Calvo et al (2014), during development and validation of the rCMPS-F, observed high rCMPS-F scores associated with elevated "general impression" (demeanor) scores (Calvo et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations